Pengembangan Media Pembelajaran Interaktif Pariwisata Budaya Dengan Metode Multimedia Development Life Cycle - Andi Sano, Andreas Novito; Dian Maharani; Tegar Alamsyah; Hasby Arrahman; Dasril Aldo (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2024)
Education about Indonesian culture and heritage faces challenges with ineffective learning models, which tend to focus on storytelling skills but need more student engagement. Local culture is also increasingly influenced by Western culture, especially among teenagers. This research aims to design interactive multimedia learning media that are engaging and effective in introducing Indonesian culture and heritage. The method used is the Multimedia Development Life Cycle (MDLC), involving stages of concept development, design creation, content gathering, application development, and testing and distribution. The research results indicate that the developed interactive learning media features text, audio, images, and videos accessible to all users, particularly children. Alpha and beta testing show that this learning media performs well and is highly suitable for use, scoring 4,73 out of 5 on the assessment scale. This learning media hopes to enhance users' understanding of Indonesian culture and heritage and support their preservation in the modern era. Â Keywordsâ€”Culture, Heritage, Interactive Learning Media, MDLC